The Curriculum in an Adventist University - B. de Korniejczuk, Raquel (2012)
In this work is showed the need of a curriculum of a Adventist Institution, whereeach student can have a Christian worldview about their life and field by concludingtheir studies. So, in this work is presented the curriculum- elements, theessential elements of the Adventist education so that the curriculum of an Institutioncan be considered very important in the fulfillment of the desired goals.On the other hand, the experts in Education field, points out that each students‘experiences and in its totality will do a great impact in their life and determinetheir future as a professional and how they can see their profession, their faith,their family and their mission.